∫ 0 1 x 5 ( 2 − x ) 4 d x
If the above integral can be expressed in the form b a , where a and b are coprime positive integers, find a + b .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Faster way to do it? Multiplying out like that is a pain. I modeled the problem off the Beta function changed part of it, maybe there's a way to do it faster using Beta function.
I used Beta function as mentioned by Hobart Pao .
I = ∫ 0 1 x 5 ( 2 − x ) 4 d x Let 2 − x = 1 + sin θ ⟹ x = 1 − sin θ ⟹ d x = − cos θ d θ = ∫ 0 2 π ( 1 − sin θ ) 5 ( 1 + sin θ ) 4 cos θ d θ = ∫ 0 2 π ( 1 − sin θ ) ( 1 − sin 2 θ ) 4 cos θ d θ = ∫ 0 2 π ( 1 − sin θ ) cos 9 θ d θ = ∫ 0 2 π ( sin 0 θ cos 9 θ − sin θ cos 9 θ ) d θ = 2 1 ( B ( 2 1 , 5 ) − B ( 1 , 5 ) ) = 2 1 ( Γ ( 2 1 1 ) Γ ( 2 1 ) Γ ( 5 ) − Γ ( 6 ) Γ ( 1 ) Γ ( 5 ) ) = 2 4 ! ( 9 ! ! π 2 5 π − 5 ! 1 ) = 6 3 0 2 5 6 − 1 0 1 = 6 3 0 1 9 3
⟹ a + b = 1 9 3 + 6 3 0 = 8 2 3
Nicely done! That's what I was looking for.
It will be better to inform that a/b is in the simplest form
I did. a and b are coprime positive integers, meaning that the only factor they share is 1.
Problem Loading...
Note Loading...
Set Loading...
∫ 0 1 x 5 ( 2 − x ) 4 d x = ∫ 0 1 x 5 ( 2 4 + x 4 − 4 × 2 3 × x − 4 × 2 × x 3 + 6 × 2 2 × x 2 ) d x = ∫ 0 1 ( 1 6 x 5 + x 9 − 3 2 × x 6 − 8 × x 8 + 2 4 × x 7 ) d x = [ 6 1 6 x 6 + 1 0 x 1 0 − 7 3 2 x 7 − 9 8 x 9 + 8 2 4 x 8 ] 0 1 = 6 1 6 + 1 0 1 − 7 3 2 − 9 8 + 8 2 4 − 0 = 3 0 2 4 0 8 0 6 4 0 + 3 0 2 4 − 1 3 8 2 4 0 − 2 6 8 8 0 + 9 0 7 2 0 = 3 0 2 4 0 9 2 6 4 = 6 3 0 1 9 3 ⟹ b a = 6 3 0 1 9 3 ∴ a + b = 1 9 3 + 6 3 0 = 8 2 3 .